Proceedings of the 2017 International Conference on Organizational Innovation (ICOI 2017) 2017
DOI: 10.2991/icoi-17.2017.18
|View full text |Cite
|
Sign up to set email alerts
|

Customer Loyalty Analysis of Online Travel Agency App with Customer Satisfaction as A Mediation Variable.

Abstract: In the current era, the internet plays critical roles in people's life. Several activities that used to be done traditionally (offline) have now enter the virtual world. This phenomenon brings a huge change in people's lifestyle who want something has done faster and easier than before. Just like a shopping behavior, customers' activity in travelling is also changed. Nowadays, a lot of people don't go to the traditional of physical (offline) travel agencies. They have switched them with online travel agency ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…The similar conclusion has been attained in several other studies that responsiveness to complaint handling is a major factor for the customer satisfaction in case of the airline industry (Etemad-Sajadi & Bohrer, 2019;Lee, 2017). Numerous studies have demonstrated that responsiveness to complaints brought the customer closer, satisfied the customer, and that the satisfied customer led to the increase of such economic aspects as business operations, sales, growth, and profits of the airline industry (Karamata et al, 2017;Dwikesumasari & Ervianty, 2017;Dennett et al, 2000). However, the higher level of service quality bring the customer loyalty and that service quality can be delivered through hospitality and responsiveness to customer complaint handling at the right time (Servera-Frances & Piqueras-Tomas, 2019; Lee, 2017;Metwally, 2013).…”
Section: Responsiveness To Complaints and Customer Satisfactionsupporting
confidence: 77%
See 4 more Smart Citations
“…The similar conclusion has been attained in several other studies that responsiveness to complaint handling is a major factor for the customer satisfaction in case of the airline industry (Etemad-Sajadi & Bohrer, 2019;Lee, 2017). Numerous studies have demonstrated that responsiveness to complaints brought the customer closer, satisfied the customer, and that the satisfied customer led to the increase of such economic aspects as business operations, sales, growth, and profits of the airline industry (Karamata et al, 2017;Dwikesumasari & Ervianty, 2017;Dennett et al, 2000). However, the higher level of service quality bring the customer loyalty and that service quality can be delivered through hospitality and responsiveness to customer complaint handling at the right time (Servera-Frances & Piqueras-Tomas, 2019; Lee, 2017;Metwally, 2013).…”
Section: Responsiveness To Complaints and Customer Satisfactionsupporting
confidence: 77%
“…According to Karamata et al (2017), and Majumdar (2005), the customer retention and loyalty can only be possible if the customer is satisfied, and ultimately, the airline company would generate augmented profits and future economic prospects. Thus, based on previous studies, such as Chen and Jai (2019), Cronin and Taylor (1992), Dwikesumasari and Ervianty (2017), and Fornell (1992), it is concluded that retention and loyalty of existing customers are the key factor for the success of the airline industry. According to Blodgett et al (1995), and Chow and Tsui (2017), the customer satisfaction and customer loyalty are interchangeable in high quality service organizations; moreover, the customer satisfaction leads to the customer loyalty through positive word of mouth in the airline industry.…”
Section: Customer Satisfaction and Customer Loyaltymentioning
confidence: 93%
See 3 more Smart Citations